Are Ziswaf Expenditures and Depression Symptoms Correlated? Evidence from Indonesia - Fadhillah, Hafizh; Ar'rabani, Akbar Dzidan (International Journal of Zakat, 2024)
This research investigates the relationship between ziswaf expenditure and depression symptoms using the IFLS5 data. Depression was assessed using the 10-item Center for Epidemiologic Studies-Depression Scale Revised (CESD-R-10). The scores were converted into logit form using the Rasch model. This study finds a statistically significant negative correlation between ziswaf expenditure and the presence of severe depression symptoms using the OLS-multiple linear regression. A higher level of ziswaf expenditure was associated with lower scores in depression symptoms among muslim in Indonesia.